2019
DOI: 10.3390/pr7010041
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Hexavalent Chromium from Wastewater with Electro-Reduction

Abstract: Removal of hexavalent chromium had attracted much attention as it is a hazardous contaminant. An electrocoagulation-like technology electro-reduction was applied. The chromium (VI) in the wastewater was reduced to chromium (III) by the electron supplied by electricity power and Fe2+, formed from corrosion of steel electrodes in acidic conditions. The mechanism and parameters affecting the reaction were investigated. The results optimized by response surface methodology indicated that the influence of single fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 32 publications
2
49
0
1
Order By: Relevance
“…The effect of reaction temperature on the reduction efficiency was conducted while other conditions kept constant: initial concentration of chromium (VI) of 1.000g/L, current density of 50 A/m 2 , concentration of H2SO4 of 100 g/L and stirring rate at 500 rpm. The results showed in Figure 3 indicated that the reduction of chromium (VI) could be easily achieved at higher reaction temperature (≥50 ℃), which was partial consistent with recent study [8]. High temperature would decrease the diffusion resistance and favor the contact of free electron and chromium (VI) resulting in high reduction efficiency.…”
Section: Effect Of Reaction Temperaturesupporting
confidence: 88%
See 4 more Smart Citations
“…The effect of reaction temperature on the reduction efficiency was conducted while other conditions kept constant: initial concentration of chromium (VI) of 1.000g/L, current density of 50 A/m 2 , concentration of H2SO4 of 100 g/L and stirring rate at 500 rpm. The results showed in Figure 3 indicated that the reduction of chromium (VI) could be easily achieved at higher reaction temperature (≥50 ℃), which was partial consistent with recent study [8]. High temperature would decrease the diffusion resistance and favor the contact of free electron and chromium (VI) resulting in high reduction efficiency.…”
Section: Effect Of Reaction Temperaturesupporting
confidence: 88%
“…The reduction of chromium (VI) in the process was acid-dependent and higher chromium (VI) reduction efficiency could be achieved at high acid concentration. The acceleration of Cr(VI) reduction in the system at the high acid concentration could be attributed to that the chromium (VI) species were more easily being reduced in acidic conditions than in neutral/ alkaline conditions according to Equation (7) and (10) [8]. And the molar fraction of the Cr2O7 2-was drastically increased with increasing acid concentration according to Equation (9).…”
Section: Effect Of Concentration Of H2so4mentioning
confidence: 96%
See 3 more Smart Citations